Modified drosophila optimization algorithm for managing re-sources in cloud environment - Kukreja, Shilpa; Dalal, Surjeet; ., . (International Journal of Engineering and Technology, 2018)
Optimizing a problem is common among the researchers in all the fields. The worst case of the optimization problem is that when it is not solved by putting lots of efforts and human capital is spoiled in dealing with the problem. So, to search for the optimal solution of a problem is becoming a tedious job for the scholars. Many algorithms have been applied to solve these long-standing complex problems. In this paper, Drosophila Food search optimization (DFO) Algorithm is applied, which explores its vision foraging behavior in the global optimization process. The objective behind the use of DFOA is to achieve fast computation, maximizing resource utilization and minimizing makespan. The survey of our work presents the state-of-the-art in recent research.Â Â